EKSPERIMENTASI MODEL PEMBELAJARAN TTW DAN TPS PADA MATERI BANGUN RUANG SISI DATAR DITINJAU DARI KEMAMPUAN PENALARAN MATEMATIS SISWA - Arie Purwa Kusuma; Budiyono Budiyono; Dewi Retno Sari S (Jurnal Pembelajaran Matematika, 2015)
Abstract: The objectives of this research were to investigate the effect of the learning models on the learning achievement in Mathematics viewed from the reasoning abilities of the students. The models compared were the cooperative learning model of the Think Talk Write (TTW) type, the Think Pair Share (TPS) type, and the conventional learning model. This research used the quasi experimental research method with the factorial design of 3 x 3. Its population was all of the students in Grade VIII of State Junior Secondary Schools of Wonosobo regency in Academic Year 2013/2014. The samples of the research were taken by using the stratified cluster random sampling technique. They consisted of 278 students, and were divided into three classes, namely: 93 in Experiment Class 1, 93 in Experiment Class 2, and 92 in Control Class. The instruments employed to gather the data of the research were test of learning achievement in Mathematics and test of mathematical reasoning ability. The data of the research were analyzed by using the two-way analysis of variance with unbalanced cells. The results of the research are as follows. 1) The cooperative learning model of the TTW type results in a better learning achievement in Mathematics than the cooperative learning model of the TPS type and the conventional learning model, and the cooperative learning model of the TPS type results in a better learning achievement in Mathematics than the conventional learning model. Such results indicate the same result for each category of the mathematical reasoning abilities. 2) The students with the high mathematical reasoning have a better learning achievement in Mathematics than those with the moderate and low mathematical reasoning abilities, and the students with the moderate reasoning ability have a better learning achievement in Mathematics than those with the low mathematical reasoning ability. Such results signify the same result for each category of the learning models.Keywords: TTW, TPS, mathematics reasoning ability, mathematics achievement